Numerical Study of Lymph Mechanics - DANIEL WATSON (2021)
Methods taken from engineering and computer science were applied to the lymphatic system. Starting with a 3D analysis of a single subject-speciﬁc lymphatic valve. A mechanism was presented to explain previous experimental results showing the eﬀect of trans-mural pressure on the pressure required to close lymphatic valves. The impor-tance of wall motion in future FSI studies of lymphatic valve dynamics were identiﬁed. Previous approaches to lumped modelling of the lymphatic system were considered and modiﬁcations were proposed. A less-idealised valve model, incorporating trans-mural dependent bias, was proposed as well as a method of allowing self-organised contrac-tion through a stretch-dependent frequency of contraction. A network of the superﬁcial lymphatics of the upper-limb was reconstructed from an anatomical sketch. The net-work was used in conjunction with the lumped model to produce a 421 vessel lymphatic model consisting of 17,706 lymphangions. Several issues which impede large network scale modelling of the lymphatic system are identiﬁed. A simpliﬁed patient-speciﬁc biphasic model of lymphoedema was proposed and used to develop a novel shape-based metric for lymphoedema. A statistically signiﬁcant relationship between the metric and the presence of lymphoedema was found.